Armed conflict and the changing role structure of women in Nepal (2011)
This paper is an attempt to understand the conflict that affected Nepal for a decade, with specific reference to the changing role structure of women. It explores the changes that have taken place in the society post conflict and the strategic roles that women can play. My focus on Nepal allows for an understanding of armed conflict and its repercussions through women’s experiences of coping with the changes that they have to adapt to. It also highlights the past movements in Nepal led by women which defines the strength that women have as political and social agents.